MENINGKATKAN KEMAMPUAN MENGHAFAL SURAT-SURAT PENDEK DENGAN METODE TALAQQI PADA USIA 5-6 TAHUN DI RA PERWANIDA KROMPOL BRINGIN - Eko Prasetiyo; Aisyah Layli (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2021)
ABSTRACT Raudhatul Athfal (RA) is the level of Early Childhood Education in the formal pathway that organizes general and Islamic education programs. The purpose of this study is to try to find out how children can be happy with learning to memorize short letters so that children are able to memorize short letters properly and correctly. This study uses a qualitative approach with a qualitative descriptive type with a classroom action research approach, namely the data obtained in the form of written or spoken words from the results of observations and interviews / direct practice at the time of the study. The research sample amounted to 15 students, data collection techniques used observation, interviews, documentation and reflection techniques. Based on the results of the study, it was shown that increasing the ability to memorize using the talaqqi method at RA Perwanida Krompol in this study was successful in improving the memorization of short letters. It is proven by an increase in the ability to memorize short letters in children who initially did not achieve well, then after doing research using the talaqqi method many children reached the very good category.